2012
DOI: 10.1016/s1995-7645(12)60166-7
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin enhances superoxide dismutase activity and inhibits RAGE and VEGF expression in retinas of STZ–induced early diabetic rats

Abstract: Puerarin is able to enhance SOD activity, and inhibit RAGE and VEGF expressions in retinas of STZ-induced early diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Previous studies have shown that a large number of flavonoids possess protective effects on diabetes-induced retinal pathological alterations, including vascular hyperpermeability, vascular endothelial cell injury, and excessive retinal proinflammatory cytokines (Chen et al, 2012;Chung et al, 2005;Kumar et al, 2013Kumar et al, , 2012Li et al, 2013;Nakajima et al, 2001;Yang et al, 2009). Present study was designed to explore the potential effect of silybin, also a kind of flavonoid compound, on retinal blood vessels in diabetes that was induced in rats with STZ plus high-fat diet.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that a large number of flavonoids possess protective effects on diabetes-induced retinal pathological alterations, including vascular hyperpermeability, vascular endothelial cell injury, and excessive retinal proinflammatory cytokines (Chen et al, 2012;Chung et al, 2005;Kumar et al, 2013Kumar et al, , 2012Li et al, 2013;Nakajima et al, 2001;Yang et al, 2009). Present study was designed to explore the potential effect of silybin, also a kind of flavonoid compound, on retinal blood vessels in diabetes that was induced in rats with STZ plus high-fat diet.…”
Section: Discussionmentioning
confidence: 96%
“…[13] Puerarin, a form of herbal medicine, which has shown that it attenuates brain damage after ischemic stroke in rats. [45814] Previous studies have demonstrated that puerarin has multiple therapeutic effects involving anti-apoptosis,[14] anti-inflammation[4] anti-oxidative stress,[1516] anti-excitotoxicity,[16] activated potassium channel[3] and increase cerebral blood flow,[17] indicating puerarin might be a novel candidate for new drug development. However, all these published studies focused only on pre-stroke or early puerain treatment in acute brain tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PR significantly reduced the elevated levels of VEGF-C in DMBA rats, suggesting that it might inhibit breast tumor formation by downregulating vascular angiogenesis factors in rat DMBA-induced breast tumors. An association between puerarin and VEGF has been reported in several studies, and puerarin has been suggested to suppress the vascularization of ectopic endometrial tissues stimulated by 17β-estradiol (Wang et al, 2011) and to inhibit VEGF expression in retinas of streptozotocin-induced early diabetic rats (Chen et al, 2012a). Other reports suggest that puerarin may induce therapeutic angiogenesis by increasing VEGF mRNA expression in rats with myocardial infarction (Zhang et al, 2006).…”
Section: Journal Of Agricultural Sciencementioning
confidence: 94%